Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 120477 by help last updated on 31/Oct/20

Answered by Dwaipayan Shikari last updated on 31/Oct/20

f(x)−f(x−2)=6  f(2)−f(0)=6  f(2)=7   ,  f(1)=4  f(0)=1        And  f(3)−f(1)=6  ⇒f(3)=10  f(n)=1+(n)3  f(71)=1+71.3=214

f(x)f(x2)=6f(2)f(0)=6f(2)=7,f(1)=4f(0)=1Andf(3)f(1)=6f(3)=10f(n)=1+(n)3f(71)=1+71.3=214

Answered by Ar Brandon last updated on 31/Oct/20

f(x)=f(x−2)+6, f(0)=1, f(1)=4  f(2)=f(0)+6=7, f(3)=f(1)+6=10  f(4)=f(2)+6=13, f(5)=f(3)+6=16  ⇒f(x)=3x+1 ⇒ f(71)=3(71)+1=214

f(x)=f(x2)+6,f(0)=1,f(1)=4f(2)=f(0)+6=7,f(3)=f(1)+6=10f(4)=f(2)+6=13,f(5)=f(3)+6=16f(x)=3x+1f(71)=3(71)+1=214

Commented by Dwaipayan Shikari last updated on 31/Oct/20

Oh it was a mistake of mine

Ohitwasamistakeofmine

Commented by Ar Brandon last updated on 31/Oct/20

Oh it was a mistake from mine

Ohitwasamistakefrommine

Commented by Ar Brandon last updated on 31/Oct/20

����Hi

Terms of Service

Privacy Policy

Contact: info@tinkutara.com